2018
DOI: 10.1186/s13362-018-0044-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimal logistics strategy to distribute medicines in clinics and hospitals

Abstract: This document presents a methodology for the optimal selection of the vehicle fleet necessary to distribute medical products from the company's storage center to many intermediate transfer nodes, and from these to a group of public hospitals. The problem addressed is a real case presented by a company that provides logistics services in the Mexican Republic. An algorithm that incorporates three modified mathematical models was designed for its solution. A version of the Dijkstra algorithm was modified for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…1. Note that Cadenillas [17] proved the verification theorem (Theorem 3.1 in the literature), which states that the solution to HJBQVI (12) under the QVI control (16) through (18) is in fact the value function (11) and the QVI control is the optimal impulse control. Thus, if we could solve the HJBQVI (12), then we are able to obtain the optimal impulse control.…”
Section: Optimal Controlmentioning
confidence: 98%
See 2 more Smart Citations
“…1. Note that Cadenillas [17] proved the verification theorem (Theorem 3.1 in the literature), which states that the solution to HJBQVI (12) under the QVI control (16) through (18) is in fact the value function (11) and the QVI control is the optimal impulse control. Thus, if we could solve the HJBQVI (12), then we are able to obtain the optimal impulse control.…”
Section: Optimal Controlmentioning
confidence: 98%
“…The boundary condition for the HJBQVI is V (0) = 0, which means that no problem arises when there is no population. The left part in "min" operator in the HJBQVI (12) corresponds to the situation where no intervention should be performed, while the right part corresponds to the situation where the intervention should be performed immediately. The following lemma gives the upper and lower bound of V .…”
Section: Hamilton-jacobi-bellman Quasi-variational Inequalitymentioning
confidence: 99%
See 1 more Smart Citation
“…The process becomes iterative until it reaches the convergence. For the design of the clusters the method mentioned in [19] is used. Here, the use of radial distribution was used due to the transportation costs of the product and the characteristics of it.…”
Section: The Clustering and Location Of Biorefineries Modelmentioning
confidence: 99%
“…The variety of applications covers from the location of banks [3,7,10,11,22,23] industrial facilities [2,4,8,19,25]. A review on location of facilities and supply chain can be found in [16].…”
Section: Introductionmentioning
confidence: 99%